Studi Simulasi Sistem Monitoring Air Proses Produksi Berbasis Borland Delphi Untuk Dunia Industri - Wahyu Hadikristanto (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Water monitoring system is a solution offered to anticipate problems that occur in some industries, using the development of monitoring system is expected to mengeffesiensikan working time, a simple simulation is exposed through prototype and programming language Borland Delphi (boland Delphi 7), the monitoring system is a device simple software and can be used to regulate or control the temperature and water level of a quenching tub which is a part cooling tub (appliance). In realizing this, using the method approach, the method used for the preparation of research that is the method of experiment. In software design using Delphi programming language modified with assembler language to translate the input or output on the pheripheral through the parallel port. The performance of the system simulation device acknowledges the water level so that the process material is not NG, with the help of the parallel port interface via the LPT1 address 378 will provide output to the driver circuit. Utilization of this interface to maximize the work of the parallel port should use a PPI (programmable peripheral interface) IC because the IC is designed to blind the input port and parallel computer output which only has 8 bits can be 24 bits, so it can accept larger I / O (many ). Keywords: Water Monitoring System, Quenching